Book review: Pulk, Kätlin and Koris, Riina (Eds.). Generative AI in higher education. The good, the bad, and the ugly - Thomas Wilson (Information Research: An International Electronic Journal)
Pulk, Kätlin and Koris, Riina (Eds.). (2025). Generative AI in higher education. The good, the bad, and the ugly. Edward Elgar. 2025. 214 p. ISBN: 9781035326013